Transformation of Children's Character through Digital Approaches in Primary Education - Wiwik Dyah Aryani; Oki Dermawan; Imam Asrofi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
Integrating digital approaches into character education in primary schools has become increasingly significant, particularly in response to the COVID-19 pandemic. This transition involved adopting digital technologies and innovative pedagogical methods to enhance character education amidst the challenges of remote learning environments. Key components included using e-learning technologies and the development of electronic educational resources, which promoted independent student work and supported character development. Despite challenges such as limited digital literacy and device access, character education remained a vital goal, supported by strategies that leveraged online resources and involved parental engagement. Digital game-based learning proved effective in engaging students and fostering a student-centred learning environment, reinforcing its role in enhancing engagement and character development. Integrating digital technologies was crucial for addressing diverse student needs and improving teacher competencies, leading to better educational outcomes. The Ministry of Education and Culture of Indonesia developed a 15-year roadmap to improve educational quality and digital literacy, emphasizing the need for adaptation to a digital society. This study employed qualitative descriptive analysis through a literature review to explore the implementation of digital character education in primary schools. The findings suggested that effective digital character education required role modelling, a supportive environment, and consistent habituation, all essential for nurturing students' character in a digital age.Â